Chukfi Rabbit's big, bad bellyache : a trickster tale - Rodgers, Greg (Cinco Puntos Press, 2014)
"Silly kids, tricks are for rabbits! Chukfi Rabbit, that is. The laziest-and hungriest-trickster rabbit there is! Deep in Choctaw Country Chukfi Rabbit is figuring out some way to avoid work at all costs. When Bear, Turtle, Fox, and Beaver agree on an everybody-work-together day to build Ms. Possum a new house, Chukfi Rabbit says he's too busy to help. Until he hears there will be a feast to eat after the work is done: cornbread biscuits, grape dumplings, tanchi labona (a delicious Choctaw corn stew), and best of all, fresh, homemade butter! So while everyone else helps build the house, Chukfi helps himself to all that yummy butter! The furry fiend! But this greedy trickster will soon learn that being this lazy is hard work! A classic trickster tale in the Choctaw tradition.